Pengaruh Aromaterapi Lemon Dan Relaksasi Genggam Jari Terhadap Penurunan Nyeri Persalinan Fase Aktif Lampung Selatan - Herlina; Nining Sriningsih (Universitas Bengkulu, 2023)
The uterine contraction and complete opening (10 cm) can cause pain in birthing stage I of active phase. The objective of this research was to find out the influence of lemonade aroma and holding fingers relaxation therapies to reduce pain of birthing stage I of active phase in Seloretno village midwifery clinic in Sidomulyo sub district of South Lampung district in 2020. This was quantitative research by using a pre-experiment approach and one group pretest-posttest design. Population was 22 birthing mothers stage I in active phase in Seloretno village midwifery clinic. Samples were of total sampling. Data were collected with observation sheets and analyzed by using univariate and bivariate analyses with t-dependent test. The research result showed that the average of pain in birthing stage I of active phase before and after lemonade therapy and holding fingers relaxation therapies were 6.77 and 4.59 respectively. Then obtained p- valuei=i0.000. Suggestions for future researchers to be able to carry out further research by expanding research variables, for example factors related to pain, increasing the population and sharpening research analysis to multivariate.